The effect of isometric exercise on intensity and duration of pain among physically inactive young females with primary dysmenorrhea - Zaid, Nik Siti Nuramiza Aisyah Nik Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Introduction: Primary dysmenorrhea (PD) is defined as recurrent, cramp-like pain occurring with normal ovulatory menses in the absence of any pelvic pathology. Isometric exercise is a subgroup of exercises, during which the muscle length and joint remain constant during contraction. To date, effectiveness of isometric exercise in reducing intensity and duration of pain is not yet established. It is hoped this study will provide in-depth knowledge on isometric exercise and its effect on PD in sedentary young females to overcome the deficiency of data on the management of PD and physical activity. Objectives: The primary aim of the study was to investigate the effect of isometric exercise on intensity and duration of PD among physically inactive young females. Methods: In this randomised controlled trial, 24 young females with primary dysmenorrhea were randomly assigned to either exercise or control groups with 12 participants in each group. While participants in the control group continued with their physically inactive lifestyle, those in the exercise group were required to perform isometric exercise for 8 weeks with 5 days per week, 2 sessions per day, 10 min per session. Pain intensity and duration of all the participants were measured at pre, mid and post-test. The intensity of pain was measured by using the Visual Analog Pain Scale (VAPS) and duration of pain was recorded in hour. The data was analysed by Mixed ANOVA, SPSS vs. 25.0. Results: After 8 weeks of isometric exercise intervention, the mean score of pain intensity (VAPS) was significantly reduced in exercise group (6.08 to 1.92) (p<0.05) and remained constant in control group (6.25 to 6.58) (p>0.05). The mean duration of pain (hours) was also significantly reduced in exercise group (10.00 to 2.00) (p<0.05) and remained constant in control group (9.25 to 9.42) (p>0.05). Conclusion: The mean intensity and duration of menstrual pain significantly reduced in exercise group compared to control group after 8 weeks of isometric exercise intervention. Hence, it can be concluded that isometric exercise appears to be an effective non-pharmacological method and provide significant positive reduction for intensity and duration of pain for primary dysmenorrhea.